WACANA INTERAKSIONAL KEBIJAKAN HARGA GABAH DAN BERAS - Akmal Afif Fatah Yasin (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2008)
Interactional discourse in media is the important term that may cause the failure on policy implementation. The aim of this study is to discover the interaction among actors of the discourse construction that they can achieve their needs to accommodate in grain and rice price policy. This study was based on the method of Teun A. van Dijk discourse analysis model. This research explains a critical perspective on food policy in liberalization era which had strong relation to the power of discourse and it determined the food prices as well. Discourse in media also has opportunity for catalyst and social engineering policy. We need to minimize hegemony of actors in order to avoid semiotic violence. This study concludes, they wish to a chieve that the food policy maker should pay attention to the interactional discourse in media if the grain and rice price policy implementation.